Repeat Offender Laws in the United States: Forms, Uses, and Perceived Value, 1983 - McDonald, William F. ([Verlag nicht ermittelbar], 1990)
This survey of prosecutors, defense attorneys, and judges in jurisdictions with sentence enhancement statutes for repeat offenders collected information about the characteristics of the laws and criminal justice professionals regarding the fairness, effectiveness, and practice of the laws. The jurisdiction file includes variables such as jurisdiction size, number of provisions in the law, number of felony cases handled under the law per year, number of defendants sentenced as repeat offenders, frequency of charging and sentencing under the law, and minimum and maximum sentences specified in the statutes. The variables in the three surveys of practitioners contain data related to their familiarity with the laws, descriptions of recent cases, and satisfaction with the new statutes.